2020
DOI: 10.1097/md.0000000000019638
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of lymphocyte monocyte ratio in patients with ovarian cancer

Abstract: Background: This study aimed to systematically assess the prognostic value of lymphocyte monocyte ratio (LMR) in patients with ovarian cancer through performing a meta-analysis. Methods: Web of Science, PubMed, EMBASE, Cochrane Library, and China National Knowledge Infrastructure databases were searched for potentially eligible studies. The baseline characteristics and relevant data were extracted. Hazard ratios with 95% confidence intervals (CIs) were combined to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In the study of Lu et al, Tang et al (31), Wang et al (32), and Li et al (33) were found to contribute to the observed heterogeneity. In another MA, exclusion of studies did not reduce heterogeneity and was above 50% (19). The publication bias was assessed based on Egger's and Begg's regression and rank correlation tests in three MAs.…”
Section: Meta-analyses On the Lymphocyte-to-monocyte Ratiomentioning
confidence: 99%
“…In the study of Lu et al, Tang et al (31), Wang et al (32), and Li et al (33) were found to contribute to the observed heterogeneity. In another MA, exclusion of studies did not reduce heterogeneity and was above 50% (19). The publication bias was assessed based on Egger's and Begg's regression and rank correlation tests in three MAs.…”
Section: Meta-analyses On the Lymphocyte-to-monocyte Ratiomentioning
confidence: 99%
“…C-reactive protein (CRP) has been validated as a predictive factor in solid tumors [57]. Moreover, lymphocyte to monocyte ratio has been related with ovarian cancer aggressiveness and clinical outcome in a number of studies [58,59]. Collectively, NLR could be combined with other systemic markers to increase the accuracy achieved.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis also indicated the presence of CD163+ TAMs was correlated with poor prognosis ( 110 ). A decreased lymphocyte-to-monocyte ratio (LMR) also indicated both poor overall and PFS in retrospective reviews ( 111 114 ).…”
Section: Innate Immunitymentioning
confidence: 99%